Ways of interaction and features of similar semantics meaningfully measure words in Chinese language - Тоқтaрбек, С. (Journal of Oriental Studies, 2017)
At the present time in higher education institution one of the main goals of teaching Chinese language is teaching students to correctly use the writing skills and speaking skills. In order to achieve this goal, at first need be installed system of Chinese language faces in the original rules, the reservation of the culture of the Chinese language. Secondly, thoughts that the speaker wants to convey to the relationships must use suitable methods of correct pronunciation. In the Chinese proverb similar meanings of counting words make parsing (or different) of the specifics of the semantics. Similar measure words with the interaction path also have their differences. At the same time, the Chinese word counting seek profitable ways of language learning.